Female Sex as a Thromboembolic Risk Factor in the Era of Nonvitamin K Antagonist Oral Anticoagulants - Mariacarla Gallù; Giulia Marrone; Jacopo Maria Legramante; Antonino De Lorenzo; Nicola Di Daniele; Annalisa Noce (Hindawi-Wiley, 2020)
Sex-specific differences have been definitively demonstrated in cardiovascular (CV) diseases. These differences can also impact on the effects of CV therapies. Female sex is recognized as an independent predictor of thromboembolic risk, particularly in older patients. Most of strokes are due to atrial fibrillation (AF). Women affected by AF have higher stroke risk compared to men. The introduction of novel oral anticoagulants (NOACs) for long-term anticoagulation completely changed the anticoagulant therapeutic approach and follow-up of patients affected by nonvalvular atrial fibrillation (NVAF). CHA2DS2-VASc stroke risk scoring in use in the current international guidelines attributes 1 point to "female sex". Besides, no anticoagulation is indicated for AF female patients without other risk factors. Interestingly, NOACs seem to normalize the differences between males and females both in terms of safety and efficacy, whereas residual higher stroke risk and systemic embolism persist in AF women treated with vitamin K antagonist anticoagulants VKA with optimal time in therapeutic range. Based on the CHA2DS2-VASc score, NOACs represent the preferred choice in NVAF patients. Moreover, complete evaluation of apparently lower risk factor along with concomitant clinical conditions in AF patients appears mandatory, particularly for female patients, in order to achieve the most appropriate anticoagulant treatment, either in male or in female patients. The present review was performed to review sex differences in AF-related thromboembolic risk reported in the literature and possibly highlight current knowledge gaps in prevention and management that need further research.